“Beside a well, one does not thirst, beside a sister, one does not despair”: Women’s Script and Sisterhoods in China (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The topic of this paper is a particular form of writing that originated in southern China – Nushu (女书). Unique in its nature, Nushu was exclusively used by women, hence its name “womenʼs script”. We will attempt to provide an analytical response to what enabled the development of a script unique to women in a strictly patriarchal, Confucian society, and, in connection with this, whether men were aware of this script and if they could use it. We will also explore how certain practices that significantly shaped the lives of women in China, including the area where Nüshu was used, were linked to this script, particularly foot binding. Furthermore, we will seek to uncover potential reasons for the development of this script in this specific region of China, as well as the factors that hindered its further spread. In addition to the script itself, we will present the lives of women in this part of China, their customs, and the supportive relationships they formed within “sisterhoods”. These sisterhoods played a crucial role in enabling women to express their voices through Nushu and support one another in a patriarchal community that was unwilling to listen to women's voices. To further expand on the topic, this study examines the prevalence of illiteracy among the local population and the intriguing paradox of women's desire to create and learn a new script. Various assumptions regarding the age of the script, spanning thousands of years, are explored, as are the legends surrounding its origin. The most well-known legend, that of the girl named Pan Qiao (盘巧), though unlikely to be historically accurate, reflects many aspects of the lives of women who practiced Nushu. A comparison between the womenʼs script, Nushu, and the standard Chinese script, Hanzi, reveals interesting findings that suggest the womenʼs script may be more practical for everyday use. Additionally, this research provides a detailed description of womenʼs lives in the region, covering topics from childhood to sisterhood, marriage, festive celebrations, and traditional customs. The paper also examines a selection of poems (known as “nuge”) written in this script, through which women expressed their thoughts and emotions. These poems are closely associated with the womenʼs script, as everything written in this script follows the same format – consisting of verses of either five or seven characters. Furthermore, this study examines how women perceived the Confucian values imposed upon them, and whether the script provided a means to navigate and improve their roles and societal positions. Lastly, this paper explores the impact of Chinaʼs tumultuous 20th century history on the development and status of Nushu, tracing how the turbulent events of the era shaped the fate of the script, and also investigates how the changing status of women influenced the development of the script and examines whether Nushu is still in use today, considering the shifts in societal attitudes and womenʼs roles. It aims to shed light on the endurance and significance of Nushu in shaping the identity and experiences of Chinese women throughout history.
Keywords: Chinese culture; nüshu; nüge; Confucianism; sisterhoods